Using Economic Mathematics to Enhance Consumer Insights: Pricing, Promotion, and Market Strategies - Adiastuty, Nuranita; Taufik, Azin; Jahidah, Nurul Siti (International Journal Administration, Business & Organization, 2024)
The increasingly competitive business environment demands a deep understanding of consumer behavior. Consumers influence the demand for products or services, making the analysis of their behavior essential for effective business strategies. This article discusses the use of economic mathematics to systematically and measurably analyze consumer behavior. Quantitative methods with descriptive and inferential analysis are used, with primary data from consumer surveys and secondary data from industry reports and e-commerce platforms. Data analysis involves linear and non-linear regression models as well as machine learning techniques such as logistic regression and decision trees. The results show that price, promotion, product quality, and consumer reviews are key factors influencing purchasing decisions. In the digital era, consumer behavior data is increasingly accessible and can be analyzed with machine learning algorithms and big data. These findings provide insights into how economic mathematics helps optimize marketing strategies and enhance competitiveness. Practical recommendations include optimizing pricing and promotion strategies as well as improving product quality. This research contributes to understanding and leveraging consumer behavior for business success